Ultrastructure of euspermatozoa and paraspermatozoa in the marine gastropod Adelomelon beckii (Caenogastropoda, Volutidae) - Arrighetti, F. (2010)
The sperm morphology of Adelomelon beckii is described by optical and transmission electron microscopy. Both euspermatozoa and paraspermatozoa were found in the specimens studied. Euspermatozoa are filiform and have an elongate nucleus capped by an acrosome. A small basal plate lies between the base of the acrosome and the nucleus. The mid-piece consists of U-shaped mitochondria wrapped helically around the central axoneme. A dense annulus at the junction of the mid-piece and glycogen piece is found, ending in a short end-piece, composed of the axoneme surrounded by a plasma membrane. Two types of paraspermatozoa are found, both vermiform but differing internally with respect to the disposition and number of axonemes, as well as to the types of secretory vesicles. We suggest the use of paraspermatozoa as a systematic character to reveal phylogenetic relationships in this family. © 2009 Springer-Verlag and AWI.